A manual three-step latent profile analysis to discover phubbing risk profiles among university students - Şimşek, Ömer; Başaran, Bülent (Frontiers in Psychology, 2025)
Phubbing, snubbing others in favor of one’s smartphone, is a growing concern among university students. This cross-sectional study aimed to identify distinct phubbing profiles among university students and examine the influence of various factors on these profiles, as well as their associations with loneliness, communication skills, and happiness. Latent profile analysis (LPA) was conducted on a convenience sample of 691 university students (71.9% female, 28.1% male; M = 22.50 years) from a state university in southeastern Turkey. The study found three unique phubbing profiles: Low (67.3%), Moderate (24%), and High (8.7%) phubbing risk. Gender and smartphone addiction were significant predictors of phubbing profiles, with females and those with higher smartphone addiction showing a higher likelihood of engaging in phubbing. Interestingly, insomnia, depression, socioeconomic status, number of friends, and frequency of social interactions did not significantly influence phubbing profiles. The study found that a higher risk of phubbing was associated with increased loneliness; however, no significant differences were observed between profiles in terms of communication skills or happiness. These findings underscore the importance of addressing smartphone addiction as a critical driver of phubbing and the potential for phubbing to exacerbate loneliness among university students. The study also suggests that future research should delve into the long-term effects of phubbing on social and psychological well-being and develop interventions targeting healthy digital behaviors.